2005
DOI: 10.1002/msc.3
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes generated by patients with rheumatoid arthritis: how important are they?

Abstract: Outcomes generated by patients as important in RA, are generalizable and inclusive. The most important (independence, pain and mobility) are routinely treated and measured. The next most important (feeling well, fatigue) are infrequently addressed and deserve urgent consideration for measurement, treatment and research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
89
0
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 15 publications
1
89
0
5
Order By: Relevance
“…However, unlike pain and disability, fatigue is rarely addressed as a treatment target in its own right, is infrequently reported separately in trials, and is not a recommended core outcome for clinical trials (1). Fatigue is a significant symptom experienced almost universally by patients with RA (88 -98%), often on a daily basis, and patients rate the impact and importance of fatigue as similar to pain (2)(3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…However, unlike pain and disability, fatigue is rarely addressed as a treatment target in its own right, is infrequently reported separately in trials, and is not a recommended core outcome for clinical trials (1). Fatigue is a significant symptom experienced almost universally by patients with RA (88 -98%), often on a daily basis, and patients rate the impact and importance of fatigue as similar to pain (2)(3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…The results of the questions evaluating the functional capacity of a patient were consistent with earlier studies. In these it has been found that patients with rheumatoid arthritis consider the ability to move to be important [10,11]. The patients in this study were also willing to pay the highest sum of money for a possible improvement of functional capacity of walking outdoors on flat ground.…”
Section: Discussionmentioning
confidence: 75%
“…The strength of the WTP method is its ability to separately emphasize the different functions in the HAQ. It has been found in earlier studies that health care professionals and RA patients emphasize different issues in the treatment outcomes [11,14]. The significance of, for instance, pain and functional deficits also differ among the patients during the different stages of the disease [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, differences have been shown between physician and patient assessments of outcomes such as pain, overall health, and physical and mental function [14]. Second, RA patients identify treatment outcomes that are not routinely measured, such as sleep, well-being, and normality [15][16][17], which may relate to disease activity.…”
Section: Introductionmentioning
confidence: 99%